Time of application and fungicide performance in the control of wheat scab Época de aplicação e desempenho de fungicidas no controle da giberela em trigo - Moreira E.N.* (2007)
The chemical control of the wheat scab can be affected by time of application and fungicide. In the 2004 growing season, the fungicides were applied in the plant growth stage of beginning of flowering, half of complete flowering and beginning of soft dough stage. In the 2005 growing season, one only fungicides application was done in the beginning of the flowering with a larger number of fungicides. The applications were done with manual spray, with CO 2 gas pressure in an outflow of 200L ha-1. The intensity of wheat scab was quantified by the incidence, severity and index of giberela. Grain yield, weight of a thousand grains and the incidence of Fusarium graminearum in the grains were also evaluated. The high porcentual of wheat scab control occurred when the application was done in the beginning of the flowering. The fungicides metconazol (0.09L i.a. ha-1), tebuconazol (0.15), trifloxystrobin+tebuconazol (0.075+0.15), azoxystrobin+ciproconazol (0.060+0.024) and pyraclostrobin+epoxiconazol (0.099+0.037) reduced significantly the intensity of giberela wheat, obtaining average control of 46% on incidence, 46.6% on severity and 71.2% on index of giberela wheat. These fungicides showed grain yield average of 23.4%, but a low efficiency on F. graminearum infection control in grains.